PENGARUH DISIPLIN KERJA, MOTIVASI KERJA , DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA MASA PANDEMIC COVID-19 - Kurniawati , Dewi (SEKOLAH PASCASARJANA PRESS, 2021)
This study aims to determine the effect of work discipline, work motivation, and work environment on employee performance. The respondent of this study were bank employee in Jakarta with a total sample of 100 respondent. This study uses multiple linear regression and coefficient of determination. The Result of this study conclude that work discipline partially affects employee performance. Partially, work motivation has no effect on employee performance, and partially the work environment has an effects on employee performance. And Work Discipline, Work Motivation, and work Environment has an effect on employee Performance.